Co-exposure of dimethomorph and imidacloprid: effects on soil bacterial communities in vineyard soil - Chang, Jean; Shen, Fo-Ting; Lai, Wei-An; Liao, Chien-Sen; Chen, Wen-Ching (Frontiers in Microbiology, 2023)
In Taiwan, pesticides dimethomorph and imidacloprid are recommended for pest control in the vineyards. Therefore, tank-mixing of these two pesticides is usually a routine practice before application. This study analyzed the influence of vineyard soil microbial flora under the recommended dosage and high dosage (100 times the recommended dosage) of dimethomorph and imidacloprid. The individual and combined application of pesticides were also tested through batches of soil incubation experiments. Four treatments, control (C), dimethomorph (DT), imidacloprid (IM), and mixed application of dimethomorph and imidacloprid (ID), were included in the experimental design. From the soil metabolism, no significant arousal was observed after two months in the recommendation dosage group, no matter whether the pesticides were being applied individually or combined. For the high dosage, imidacloprid showed a higher impact than the co-exposure treatments, showing the possible prolonged effect after its repetitive application. From PCoA analysis, pesticide treatments altered the soil ecology after two months, and the impact of imidacloprid can be explicitly observed at high dosages. At the phylum level, Acidobacteria can indicate pesticide application around the recommended dosage. It was inhibited by ID on day 7 and was augmented by all pesticides on day 63.The impact of the recommended dosage of pesticide mixtures after two months of incubation was revealed from the minor families Gemmataceae and Pirellulaceae, while the high dosage treatments impacted both the core and the minor families. Our findings verified the changes in the composition of microbial communities upon pesticide application, which would affect carbon, nitrogen, sulfur, phosphorous cycles, and contaminant removal ability within the vineyard.